Pelatihan Penyusunan Instrumen Penilaian Proses dan Hasil Pembelajaran Deep Learning - Rosmiati; Wahyu Susiloningsih; Susi Hermin Rusminati; Triman Juniarso (Universitas PGRI Adi Buana Surabaya, 2025)
This community service activity aims to enhance teachers' competence in developing assessment instruments for both the learning process and outcomes based on a deep learning approach. Deep learning emphasizes meaningful, reflective, and contextual learning, which requires more authentic forms of assessment, such as rubrics, reflection journals, observation sheets, and projects. The training was conducted over three days and involved 25 teachers from the K3S of Tarik Subdistrict, Sidoarjo Regency. The implementation method consisted of four stages: needs identification, material preparation, training and mentoring, and evaluation. Pretest and posttest results showed an increase in the average score from 62 to 85. Additionally, 90% of participants expressed satisfaction with the content and methods of the training